The development candidate therapeutic and diagnostic ligands for prion diseases - Workman, R.W. (2018)
To date there are no effective treatments for prion diseases, and these diseases are always fatal in both humans and animals. Additionally, the gold standard for diagnosis of these disease remains to be the analysis of biopsied brain tissue obtained post mortem. Consequently, there is a continued demand for therapeutics and ante-mortem diagnostics for prion diseases. This project addresses these demands by investigating candidate therapeutic and diagnostic ligands for prion diseases. This study investigated recombinant prion proteins (rPrPs) as inhibitors in scrapie and bovine spongiform encephalopathy (BSE) in vitro amplification by protein misfolding cyclic amplification (PMCA). Three ovine rPrPs with the polymorphisms VRQ, ARQ and ARR and hamster rPrP were tested against scrapie PMCA in dilution series to calculate IC50 values. The two most potent inhibitors, VRQ and ARQ, were then similarly tested against bovine spongiform encephalopathy (BSE) amplification. The most potent inhibitor of both disease types, the ovine rPrP VRQ, was then observed to inhibit a range of different scrapie and BSE strains at a fixed concentration. It is recommended that further investigation into rPrP inhibitors is performed. Strain characterisation of scrapie was investigated using rPrP inhibitors, following observations that the rPrP inhibitors generate a pattern of inhibition at a set concentration. Although this pattern of inhibition was repeatable in scrapie amplification by PMCA, this was limited to a single round of PMCA. Ultimately, this limited the application of this method to only amplification efficient prion strains and isolates. It is recommended that this method be investigated further in combination with the amplification of different isolates in substrates of different genotypes over multiple rounds of PMCA, as well as the analysis of glycoform ratios by western blotting. Here it was also identified that the imidazole used in the elution buffer for immobilised metal affinity chromatography (IMAC) can inhibit prion amplification in a strain dependent manner. This inhibition could be used in combination with the proposed method as a multi-faceted assay of prion strain characterisation. The use of next generation phage display (NGPD) to map the epitopes of autoantibodies in the sera of scrapie infected sheep was also investigated. This was performed to identify peptides that were immunoreactive to autoantibodies specific to the disease state. The identification of diagnostic peptides would then enable the development of an ante-mortem serological diagnostic test for scrapie. NGPD successfully selected immunoreactive peptides, of which 39 were selected for validation by peptide enzyme-linked immunosorbent assays (ELISAs). Although none of the peptides demonstrated diagnostic specificity by peptide ELISA, an optimised ELISA methodology was developed for future use in the validation of NGPD selected peptides. Further variations in the NGPD method, as well as validation by immunoassay, can be investigated to identify diagnostic peptides immunoreactive to scrapie specific autoantibodies.